Lingual Seizures in a Four-Year-and-Eight-Month-Old Boy - Koul, Roshan; Alam, Seema; Khanna, Rajeev (Journal of Pediatric Epilepsy, 2024)
Lingual seizures (LS) mean isolated seizures of the tongue. They are uncommon, and only a few cases have been reported. Sensory, motor, and autonomic auras or focal manifestations have a localizing value in seizures. LS have been reported with and without focal pathology in the brain. LS must be differentiated from more common conditions, like lingual tremors/dyskinesias. We report a 4-year-and-8-month-old boy with LS.
Keywords: lingual seizures; child; ICU